Dynamic Power Consumption

Discussion in 'Homework Help' started by d3ck, Apr 20, 2014.

  1. d3ck

    Thread Starter New Member

    Jul 14, 2013
    8
    0
    Hye, I have problem to understand the example of how to calculate dynamic power consumption from my class.

    Here is the question

    [​IMG]

    Where here is the suggested answer

    [​IMG]

    Part where I did not understand:

    How they relate P(A+B=1) = 1 - P(A.B=0 )
    How they relate P(Y=0)= P(A+B=1) x P(C=1)

    Thanks for the help
     
    Last edited: Apr 20, 2014
  2. d3ck

    Thread Starter New Member

    Jul 14, 2013
    8
    0
    As attached
     
  3. WBahn

    Moderator

    Mar 31, 2012
    17,748
    4,796
    I'm not familiar with the notation your author is using here. Perhaps you could explain it (and in doing so there is actually a good chance that you will get struck by lightning and realize the answer to your own confusion -- happens a lot).
     
  4. d3ck

    Thread Starter New Member

    Jul 14, 2013
    8
    0
    The question asking about dynamic power consumption of Y=(A+B).C

    Where P(A=1) is probability of input A equal to 1[HIGH], that means if the input equal to 0[LOW] it is "1-0.2=0.8" probability to get that, and so on for input B and input C.

    I know the formula is P=CL * (Probability of output transisition form 0 to 1) * VDD^2 * frequency.

    I just did not get the relation as I mention in my previous post.
     
Loading...